Cancer linked to Alzheimer disease but not vascular dementia - Roe, C M. (American Academy of Neurology, 2010)
OBJECTIVE: To investigate whether cancer is associated with Alzheimer disease (AD) and vascular dementia (VaD). METHODS: Cox proportional hazards models were used to test associations between prevalent dementia and risk of future cancer hospitalization, and associations between prevalent cancer and risk of subsequent dementia. Participants in the Cardiovascular Health Study–Cognition Substudy, a prospective cohort study, aged 65 years or older (n = 3,020) were followed a mean of 5.4 years for dementia and 8.3 years for cancer. RESULTS: The presence of any AD (pure AD + mixed AD/VaD; hazard ratio [HR] = 0.41, 95% confidence interval [CI] = 0.20–0.84) and pure AD (HR = 0.31, 95% CI = 0.12–0.86) was associated with a reduced risk of future cancer hospitalization, adjusted for demographic factors, smoking, obesity, and physical activity. No significant associations were found between dementia at baseline and rate of cancer hospitalizations for participants with diagnoses of VaD. Prevalent cancer was associated with reduced risk of any AD (HR = 0.72; 95% CI = 0.52–0.997) and pure AD (HR = 0.57; 95% CI = 0.36–0.90) among white subjects after adjustment for demographics, number of APOE ε4 alleles, hypertension, diabetes, and coronary heart disease; the opposite association was found among minorities, but the sample size was too small to provide stable estimates. No significant association was found between cancer and subsequent development of VaD. CONCLUSIONS: In white older adults, prevalent Alzheimer disease (AD) was longitudinally associated with a reduced risk of cancer, and a history of cancer was associated with a reduced risk of AD. Together with other work showing associations between cancer and Parkinson disease, these findings suggest the possibility that cancer is linked to neurodegeneration. GLOSSARY: 3MSE: = modified Mini-Mental State Examination; AD: = Alzheimer disease; ADDTC: = Alzheimer Disease Diagnostic and Treatment Centers; CHD: = coronary heart disease; CHS: = Cardiovascular Health Study; CI: = confidence interval; HR: = hazard ratio; ICD-9: = International Classification of Diseases–Ninth Revision; MCI: = mild cognitive impairment; NINCDS-ADRDA: = National Institute of Neurological and Communicative Diseases and Stroke–Alzheimer's Disease and Related Disorders Association; PD: = Parkinson disease; VaD: = vascular dementia.